Plan estratégico para la cooperativa de transportes ciudad del Coca, ubicada en el cantón Francisco de Orellana - Jaramillo Castillo, Froilán Emiliano (2014)
His thesis entitled "STRATEGIC PLAN FOR TRANSPORT UNION CITY OF COCA. LOCATED IN Francisco de Orellana Canton "whose overall objective was to propose a strategic plan for the matrix of the cooperative; why then describe the development of this research thesis: Whose general objective: To propose a strategic plan for cooperative transport Coca City Canton Francisco de Orellana, Orellana Province, and the specific objectives: Conduct situational analysis, a diagnosis of internal and external factors affecting the development of the company. For research, deductive and inductive and statistical and technical methods are used: interview addressed to members and employees of the cooperative and surveys of 350 users and 129 employees including drivers, officers and employees of offices, data collection was taken primary (employees, drivers and transport users) and secondary sources (public institutions pages, newspapers, magazines, books, previous research) sources. According to the situational analysis, the cooperative was founded on 1 June 1984, began operations with 13 units, now travels the roads of the cantons; Joya de los Sachas, Shusufindi, Lago Agrio, Loreto, Gonzalo Pizarro and others and parishes as Dayuma, Juan Montalvo, Taracoa, San Carlos, Beauty, November 3, project, etc. And has 60 bus-type units. Cooperative transport "Coca Town" is starts from June 1, 1984 with a group of visionary people from the Huaorani, Rio Napo and Free Auca date where 61 partners cohered to form cooperatives such a prestigious company with Cooperative name Coca Town, According to the evaluation of external factors, the overall rating showed a weighted total of 3.10, that indicates that the bus cooperative Coca Town, has opportunities to address threats. According to the results of the IFE Matrix, the total weighted score was 2.53 this indicates that the Cooperative Inés Coca Town has strengths and weaknesses outweigh those favoring its development without mishap. Based on the SWOT matrix that allowed high impacts propose a mission, vision and strategic objectives as built: Provide transportation services for institutions and users who wish to sightsee in the provinces of Sucumbíos and Orellana. Expand the coverage of the transport service users from surrounding areas and other provinces. Perform an advertising plan in oral and written media to publicize the services of the cooperative transportation. Ask a job training plan to stimulate employee performance and strengthen the image of the Cooperative. And respective conclusions and recommendations for the study of the strategic plan were established.